Impact of auditor rotation on audit independence. - Koo, Yee Ling. (2008)
This paper investigates the impact of mandatory rotation and the changes in incentive to earn potential economic rent on auditor independence. The case study revealed that mandatory rotation and retention increases the independence of auditors. The effect of expected litigation costs on independence was also tested and presented positive results.